Bakteri dalam Feces Cicak ditinjau dari Jumlah Bakteri dan kandungan Escherichia coli - Widhowati, Dyah (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2024)
Although the existence of house gecko around humans brings advantage as biological control of insects, but also having the risk to harm human health. 30 house gecko with body length criteria of 4 – 6 cm, which were found on the outer walls of Surabaya housing were needed to count the total bacteria and the presence of Escherichia coli bacteria in their feces. . The pour plate method was used to determine the total bacteria (Total Plate Count) in feces, by counting the number of colonies that grow on the surface of the Nutrient Agar media. The streak method to search for Escherichia coli was conducted with bacteria isolation on Eosin Methylene Blue Agar , then incubating at a temperature of 37°C for 24 hours. Colonies that grow on the media are subjected to Gram staining, testing the ability of bacteria to ferment sugar which includes: Triple Suger Iron Agar, Methy Red and Voges Proskauer media. Another test carried out was Sulfid Indol Motility Agar, Simon Citrat Agar. The average total bacteria in lizard feces is 2x108 CFU/ml. , Escherichia coli content was found in 5 lizard fecal samples.